Patisipasi Masyarakat Dalam Pemberdayaan Lingkungan - Sabiruddin Sabiruddin; Nur Alhidayatillah (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
Environmental problems are getting worse every day. One of the factors that influenced it was a very dense population. Population density will produce very large waste or garbage. If waste or waste that cannot be managed properly results in unavoidable damage to the environment. Environmental problems that occur in urban Indonesia, generally include three main things, namely: First, environmental quality tends to decrease, hygiene problems (garbage), green open space (RTH), and water and air pollution. Second, the capacity of the government apparatus is relatively inadequate in dealing with the problems faced. Third, the participation or participation of the community in managing the urban environment is still relatively low. The above problems must be overcome by increasing population awareness of existing environmental problems. Both environmental problems in urban areas, rural areas, conflict areas, disaster-prone areas, and so on.